Kenyan and Ethiopian distance runners: what makes them so good? - Wilber, R. L.; Pitsiladis, Y. P. (International Journal of Sports Physiology and Performance, 2012)
Since the 1968 Mexico City Olympics, Kenyan and Ethiopian runners have dominated the middle- and long- distance events in athletics and have exhibited comparable dominance in international cross-country and road- racing competition. Several factors have been proposed to explain the extraordinary success of the Kenyan and Ethiopian distance runners, including (1) genetic predisposition, (2) development of a high maximal oxygen uptake as a result of extensive walking and running at an early age, (3) relatively high hemoglobin and hematocrit, (4) development of good metabolic "economy/efficiency" based on somatotype and lower limb characteristics, (5) favorable skeletal-muscle-fiber composition and oxidative enzyme profile, (6) traditional Kenyan/Ethiopian diet, (7) living and training at altitude, and (8) motivation to achieve economic success. Some of these factors have been examined objectively in the laboratory and field, whereas others have been evaluated from an observational perspective. The purpose of this article is to present the current data relative to factors that potentially contribute to the unprecedented success of Kenyan and Ethiopian distance runners, including recent studies that examined potential links between Kenyan and Ethiopian genotype characteristics and elite running performance. In general, it appears that Kenyan and Ethiopian distance-running success is not based on a unique genetic or physiological characteristic. Rather, it appears to be the result of favorable somatotypical characteristics lending to exceptional biomechanical and metabolic economy/efficiency; chronic exposure to altitude in combination with moderate-volume, high-intensity training (live high + train high), and a strong psychological motivation to succeed athletically for the purpose of economic and social advancement.